054 Can randomised controlled trial data from non-epilepsy indications be included in meta-analysis for AEDs used in epilepsy? An analysis of adverse event data. Issue 3 (9th February 2012) - Shukralla, A; Tudur-Smith, C; Marson, A G
Abstract : Aim: To determine if adverse event (AE) outcomes from RCTs of AEDs across non-epilepsy indications (neuropathy & migraine) can be meta-analysed with data from epilepsy trials Method: We searched for RCTs meeting inclusion criteria. AEDs included were topiramate, gabapentin, valproate, oxcarbazepine, lacosamide and others. Extracted data were analysed using RevMan 5.0. AEs analysed were; dizziness, ataxia, headache, fatigue, nausea, somnolence, AE withdrawals and any AE. Effect size summary statistics were calculated using the Mantel-Haenszel method. Statistical heterogeneity was assessed using a random effects model generating an I2 statistic. Results: Hundred and six RCTs met inclusion criteria. When dizziness was analysed, test between indications showed no heterogeneity (I2=0%) for gabapentin, topiramate, lacosamide and lamotrigine. However, heterogeneity was significant (I2=59%) for oxcarbazepine. When fatigue was the AE outcome, there was no heterogeneity (I2=0%) when we analysed data for gabapentin, lamotrigine, lacosamide, oxcarbazepine and topiramate. When somnolence was the AE outcome, heterogeneity was insignificant for oxcarbazepine (I2=8%), lacosamide (I2=0%) and topiramate (I2=0%), but significant for gabapentin (I2=56%) and lamotrigine (I2=60%). In instances where there was significant heterogeneity, the size of relative risk was greater in the non-epilepsy indications Conclusion: AEs of AEDs from non-epilepsy trials could be used in meta-analysis due to low statistical heterogeneity for some interventions and outcomes. Nevertheless this was not the case in all AEDs or outcomes. Effect sizes were larger in the non-epilepsy indications overall.